A Systematic Review: Using Trends of Ergonomic Risk Assessment Tools - Kittijaruwattana, Jitralada; Ratcha, Mongkol; Tuprakay, Seree; Surach, Anu (Health Science Journal of Thailand, 2023)
Ergonomic risk assessment tools such as Rapid Upper Limb Assessment (RULA), Rapid Entire Body Assessment (REBA), Rapid Office Strain Assessment (ROSA), Revised NIOSH Lifting Equation (RNLE), Ovako Working Posture Analysis System (OWAS), and Agricultural Lower Limb Assessment (ALLA) have been used for identifying working posture hazardous to the health of workers. Those assessments focused on the risk of work-related musculoskeletal disorders (WMSDs), which are primary contributing factor to non-fatal injuries from working. However, applying the right tools on the right job task would help in identifying the job risk. The purpose of this study is to review and analyze the ergonomic risk assessment tools and estimate the risk of WMSDs in research data of Web of Science from 2013 to 2022. The results of this systematic review indicated that each tool has a better agreement with expert evaluation results for industries or workplaces which can provide a guideline and decrease the prevalence of musculoskeletal disorders for workers.